Interfacial fluid dynamics and transport processes - Narayanan R; Schwabe D (Berlin Springer-Verlag, 2003)
The present set of lectures and tutorial reviews deals with various topical aspects related to instabilities of interfacial processes and driven flows from both the theoretical and experimental point of views. New research has been spurred by demands for
Keywords: Fluid dynamics; Transport processes